(untitled) (Medico Legal Update, 2021)
Background:Many studies showed that epileptic seizures occur more commonly in childhood stage. Most children epileptic seizures occur, during the school day. During this seizure, the child requires immediate first aid for an epileptic seizure. Aim: The study aimed to evaluate the effect of Child-to-Child Approach of Primary School Children Regarding Epileptic Seizures First Aids. Design: A quasi – experimental design (one group pre and posttest) was used in this study. Setting: This study was conducted at six governmental primary schools at Ismailia city. Sample: A multi-stage random sample was used in this study,the total number of children was180 (both male & female)divided into two groups. Trained children group (12 child) and intervention group (168 child). Tools: Two tools were used. First tool: Interviewing questionnaire was developed by the researcher and included three parts: Socio demographic data, knowledge about epileptic seizure and its first aid measures,Students’ attitudes toward epileptic seizures. Second tool: Practical Checklist: it was used to assess the practice of student’s in relation of first aids of epileptic seizures based on the Camfield et al., (2019). The Results: Showed that there were statistically significant increases in mean scores ofknowledgesof studying sample about epileptic seizure.And showed that there were highly statistically significant increases in mean scores ofpractices. The results showed that there were statistically significant increases in mean scores of positive attitudes as well as the total score. Conclusion: The knowledge,practice, and attitude of primary school children about first aid of epileptic seizure were improved post implementation of the program compared to pre implementation of the program. Recommendation: Continuous Child-to-Child Approach for Primary School Children about first aid of epileptic seizure.